La restitution architecturale et hydraulique du rampant des Massues sur l’aqueduc de la Brévenne à Lyon et ses conséquences sur l’aval du parcours - Paul François (Gallia)
The aqueducts of the Roman world are, by virtue of their form and function, excellent laboratories for implementing interdisciplinarity between the realms of engineering and archaeology. The question raised is, of course, are we able to evaluate the quantity of water conveyed by these immense structures? The data remains difficult to interpret, especially in the absence of reliable comparative data: for example, how much water did an inhabitant of Lyon consume per day in Antiquity? Or, what was the population of the city? The determination of the flow rate using our proposed method, on the other hand, makes it possible to test the relevance of certain hypotheses advanced by architectural restoration or reconstruction of the aqueducts’ course. Indeed, it becomes possible to quickly verify whether the formulated hypotheses risk dangerously constraining the flow of the aqueduct or not.This is the approach that was used in the restitution of the overflow reservoir of the Massues rampant, in Lyon. In their current state, the remains do not allow us to determine their appearance in Antiquity or to impose the production of restorations that deviate from concepts retained elsewhere by the Roman engineers of the Lyon aqueduct network. Of the five hypotheses of restitution that we formulated, one not being compatible with the state of the remains, all ensured a maximum flow in line with that of the other Lyon siphons. Hypothesis number 4 is nevertheless the one that, morphologically, is the closest to known examples: it raises the level of the overflow reservoir to 288 m. Only an excavation east of the last preserved pile of the Massues rampant would provide new data allowing us to confirm or invalidate this hypothesis.The altitude thus reached inevitably sparks curiosity regarding the remainder of the aqueduct’s route. At such a height, an uninterrupted line of arches is reconstructed over nearly 2 km. This restitution may even cast doubt on the interpretation of certain remains of the aqueduct that would impose too steep of an incline. Better still, it allows us to formulate the hypothesis that the Brévenne aqueduct was capable of carrying water to the Fourvière hill at a height of 287.5 m and perhaps even to the Verbe Incarné fountain.